THE EFFECT OF MULTIREPRESENTATION DISCOURSE LEARNING ON STUDENTS PROBLEM SOLVING ABILITY - Tatang Herman; Tetin Artinah; Dian Usdiyana (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Solving mathematical problem for most secondary students was still a very difficult job, particularly in understanding the problem and assigning mathematical models. This research attempted to overcome the lack of mathematical problem solving skills of students by using Multi Representation Discourse model (DMR). The purpose of this research was to improve mathematical problem solving skills of junior high school students by implementing DMR model. The method of the research was quasi experiment method with control group pretest-posttest. The population of this research was 7th grade students the one of junior high school in Bandung city. From this research, the researcher randomly took two classes as sample. Instrument of this research was test for measuring the mathematical problem solving skills and a questionnaire and form observation for describing students’ respons. The result of this research shows that  mathematical problem solving skills of students who got DMR learning model is higher than that of students who got direct instruction learning. Also students show positive responses enthusiastic, excited, fun and self-confident in learning mathematics.AbstrakMenyelesaikan soal pemecahan masalah matematika bagi kebanyakan siswa SMP merupakan pekerjaan yang sulit, terutama dalam memahami masalah dan menyusun model matematika. Penelitian ini dilakukan untuk mengatasi rendahnya kemampuan pemecahan masalah matematis menggunakan model pembelajaran Diskursus Multirepresentasi (DMR). Fokus utama penelitian ini adalah mengungkap apakah peningkatan model pembelajaran DMR dapat mengatasi kesulitan siswa dalam menyelesaikan soal pemecahan masalah matematika siswa SMP kelas VII.  Metode penelitian yang digunakan dalam penelitian ini adalah metode kuasi eksperimen dengan desain kelompok kontrol pretes-postes. Populasi dalam penelitian ini adalah seluruh siswa kelas VII salah satu SMPN di Kota Bandung dengan dipilih sampel dua kelas VII. Instrumen dalam penelitian ini adalah tes untuk mengukur kemampuan pemecahan masalah matematis dan instrumen non tes berupa angket dan lembar observasi untuk memngetahui respon siswa terhadap pembelajaran yang dilakukan. Hasil penelitian menunjukkan bahwa peningkatan kemampuan pemecahan masalah matematis siswa yang mengikuti model DMR lebih tinggi dibandingkan siswa yang memperoleh pembelajaran langsung. Selain itu siswa menunjukkan respon yang positif, seperti antusias, senang dan percaya diri dalam pembelajaran matematika.